MOLECULAR DETECTION OF RANGELIA VITALII IN A DOG FROM THE CURITIBA METROPOLITAN REGION, PARANA STATE, SOUTHERN BRAZIL - Mongruel, Anna C. B.; Stedile, Simone Tostes de Oliveira; Sousa, Marlos G.; Valente, Jessica D.M.; Barbosa, Iago C.; Spanhol, Viviane C.; Sezyshta, Amanda; Weber, Luiz F. S.; Vieira, Thállitha S. W. J.; Vieira, Rafael Felipe da Costa (Archives of Veterinary Science, 2017)
Rangeliosis, caused by Rangelia vitalii, is known to causes apathy, intermittent fever, ear’s margin bleeding and anemia. Herein, we report the first molecular detection of R. vitalii infecting a dog from the Curitiba metropolitan region, Paraná State, southern Brazil. A four-year-old male mixed-breed neighborhood dog, presenting apathy, weight loss, and ear’s margin bleeding, was referred for clinical care at the Veterinary Teaching Hospital of the Universidade Federal do Paraná. Sequencing of the piroplasm positive sample showed ≥99% identity with R. vitalii 18S rDNA sequence deposited in GenBank. Further studies are needed to elucidate the pathogenicity, competence vector of ticks and epidemiology of this protozoa the State of Paraná.